Colonize, radiate, decline: Unraveling the dynamics of island community assembly with Fijian trap‐jaw ants. (10th May 2020) - Liu, Cong; Sarnat, Eli M.; Friedman, Nicholas R.; Hita Garcia, Francisco; Darwell, Clive; Booher, Douglas; Kubota, Yasuhiro; Mikheyev, Alexander S.; Economo, Evan P.
Abstract: The study of island community assembly has been fertile ground for developing and testing theoretical ideas in ecology and evolution. The ecoevolutionary trajectory of lineages after colonization has been a particular interest, as this is a key component of understanding community assembly. In this system, existing ideas, such as the taxon cycle, posit that lineages pass through a regular sequence of ecoevolutionary changes after colonization, with lineages shifting toward reduced dispersal ability, increased ecological specialization, and declines in abundance. However, these predictions have historically been difficult to test. Here, we integrate phylogenomics, population genomics, and X‐ray microtomography/3D morphometrics, to test hypotheses for whether the ecomorphological diversity of trap‐jaw ants ( Strumigenys ) in the Fijian archipelago is assembled primarily through colonization or postcolonization radiation, and whether species show ecological shifts toward niche specialization, toward upland habitats, and decline in abundance after colonization. We infer that most Fijian endemic Strumigenys evolved in situ from a single colonization and have diversified to fill a large fraction of global morphospace occupied by the genus. Within this adaptive radiation, lineages trend to different degrees toward high elevation, reduced dispersal ability, and demographic decline, and we find no evidence of repeated colonization that displaces the initial radiation. Overall these results are only partially consistent with taxon cycle and associated ideas, while highlighting the potential role of priority effects in assembling island communities.